CLINICAL CHARACTERISTICS AND SHORT-TERM OUTCOMES OF NEONATES WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY TREATED WITH THERAPEUTIC HYPOTHERMIA – SINGLE CENTER EXPERIENCE FROM SERBIA: THERAPEUTIC HYPOTHERMIA IN NEONATES - Biljana, Medjo (Medical Research, 2024)
Aim: This study aimed to report clinical characteristics and short-term outcomes of neonates with hypoxic-ischemic encephalopathy (HIE) managed with hypothermia. Furthermore, we analyzed factors associated with short-term outcomes.Material and Methods: We conducted a single-center retrospective study including neonates with HIE treated with hypothermia who survived hospital discharge. The short-term outcomes were normal or abnormal neurological examination findings at discharge. Results: Forty-five neonates with HIE treated with hypothermia were identified. Median Apgar score at 1 min. was 3 (range 0-7), at 5 min. 5 (range 1-10), while the median blood pH in the first postnatal hour was 6.94 (range 6.8-7.2). On admission, more neonates had moderate than severe encephalopathy according to the modified Sarnat classification (77.8% vs. 22.2%, p
Keywords: Neonates, Hypoxic-ischemic encephalopathy, Therapeutic hypothermia